Examining Distributed Leadership Practices by School Grade Configuration. Issue 2 (2nd April 2020) - Modeste, Marsha E.; Kelley, Carolyn J.
ABSTRACT: In this study, we apply a distributed leadership framework to better understand the nature of leadership practices distributed in schools by grade configuration. In this analysis we examine the following research question: What are the differences between school-level grade configuration (elementary school or secondary school) and the extent and distribution of leadership practices in the school? This study uses multilevel confirmatory factor analysis to examine leadership practice in schools using the Comprehensive Assessment of Leadership for Learning.